Hiding in the bathroom : an introvert's roadmap to getting out there (when you'd rather stay home) - Aarons-Mele, Morra (Dey St., an imprint of William Morrow, 2017)
The marketing guru and host of the Forbes.com podcast of the same name challenges popular theories about the secrets to professional success to outline practical tips for building strong relationships and enabling achievements on one's own terms. --